2014
DOI: 10.1186/s12870-014-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the low-molecular-weight glutenin subunit allele Glu-A3a of wheat (Triticum aestivumL.) significantly reduces dough strength and breadmaking quality

Abstract: BackgroundLow-molecular-weight glutenin subunits (LMW-GS), encoded by Glu-3 complex loci in hexaploid wheat, play important roles in the processing quality of wheat flour. To date, the molecular characteristics and effects on dough quality of individual Glu-3 alleles and their encoding proteins have been poorly studied. We used a Glu-A3 deletion line of the Chinese Spring (CS-n) wheat variety to conduct the first comprehensive study on the molecular characteristics and functional properties of the LMW-GS allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…The LDN(DIC‐1A) line showed alleles Glu‐A3a* and Glu‐B3b ; however, the LDN(DIC‐1B) line had alleles Glu‐A3b and Glu‐B3c* . Due to the considerable allelic variation observed at the Glu‐3 loci and differences in the genetic background of the plant materials, it is generally difficult to determine precisely functional properties of individual alleles in wheat genotypes . Generally, the LMW‐GS encoded by the Glu‐A3 locus have a more advantageous influence on bread‐making performance than the LMW glutenins encoded by the Glu‐B3 locus .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LDN(DIC‐1A) line showed alleles Glu‐A3a* and Glu‐B3b ; however, the LDN(DIC‐1B) line had alleles Glu‐A3b and Glu‐B3c* . Due to the considerable allelic variation observed at the Glu‐3 loci and differences in the genetic background of the plant materials, it is generally difficult to determine precisely functional properties of individual alleles in wheat genotypes . Generally, the LMW‐GS encoded by the Glu‐A3 locus have a more advantageous influence on bread‐making performance than the LMW glutenins encoded by the Glu‐B3 locus .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the LMW‐GS encoded by the Glu‐A3 locus have a more advantageous influence on bread‐making performance than the LMW glutenins encoded by the Glu‐B3 locus . According to literature data, LMW‐GS encoded by alleles Glu‐A3b and Glu‐B3b, found in LDN, have a significant effect on dough strength and bread‐making quality …”
Section: Resultsmentioning
confidence: 99%
“…The LMW B‐subunits are the most abundant among LMW‐GS in mature grains and have the greatest impact on wheat processing qualities . Recently, our study confirmed that the deletion of Glu‐A3a and Glu‐B3h , encoding abundant B‐subunits in the common wheat variety Chinese Spring and CB037C, respectively, significantly reduces dough strength and breadmaking quality, indicating the important roles of LMW B‐subunits in gluten formation. In addition, one new 1S l ‐encoded B‐subunit was highly expressed, and may make a major contribution to dough quality .…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between allelic variations of Glu‐3 and breadmaking quality in common wheat are well established . Recent studies have shown that Glu‐A3a and Glu‐B3h contribute to superior flour quality . The linkage of specific LMW‐GS proteins with all Glu‐3 gene haplotypes makes it possible to discern the roles of individual LMW‐GS in wheat flour functionality and develop new lines with improved quality .…”
Section: Introductionmentioning
confidence: 99%
“…used a set of Aroona NILs of bread wheat to clarify the contribution of each allele to processing quality, and showed that alleles Glu-A3b, Glu-A3d, Glu-B3g , and Glu-B3f make significant contributions to mixograph properties. More recently, Zhen et al 22. used a natural mutation at the Glu-A3 locus to study the function of the Glu-A3a allele in bread wheat, and found that Glu-A3a significantly affects dough strength and breadmaking quality.…”
mentioning
confidence: 99%